The growth and physiological responses of tambaqui Colossoma macropomum fed on the high dose of clove oil-supplemented diet - Andi Tiara Eka Diana Puteri; Dedi Jusadi; Sri Nuryati (Jurnal Akuakultur Indonesia)
ABSTRACT